Prediction of adolescent happiness based on spiritual lifestyle with the mediation of mental health - Beyk, Hamideh; Dehaghan, Hengameh; Farahmand, Shohreh; Bahador, Elham (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Happiness is one of the constructs proposed in positive psychology, which is related to many concepts in psychology. The aim of the present study was to predict the happiness of teenagers based on spiritual lifestyle with the mediation of mental health. Methods:The research design was a correlational type in which happiness was the dependent variable, spirituality was the independent variable, and mental health was the mediating variable. The statistical population of students were studying in high schools in Tehran, and 300 people were selected by cluster sampling. The tools included Hall and Edwards’ spirituality questionnaire (1996), Schneider’s life expectancy questionnaire (2002) and revised Oxford happiness scale (2001). The data were analyzed by path analysis. Results: The results show that spirituality and mental health are predictors of happiness and mental health has a relative mediating role in predicting happiness. Mental health is also predicted by spirituality. Conclusion: In the end, it was concluded that strategic hope completely mediates between the level of satisfaction and lack of negative feelings with spiritual lifestyle, and functional hope mediates partially between perception management and despair.